The Influence of Islamic Celebrity Endorser, Halal Labels and Product Quality on Purchasing Intention of Wardah Cosmetics : Pengaruh Islamic Celebrity Endorser, Label Halal dan Kualitas Produk Terhadap Minat Beli Kosmetik Wardah - Ananda Ilmi Wahidyah; Fitri Nur Latifah (Universitas Muhammadiyah Sidoarjo, 2021)
This study was used to determine the effect of Islamic celebrity endorser, halal label and product quality on interest in buying Wardah cosmetics at Muhammadiyah University students of Sidoarjo using quantitative methods with 98 respondents who were taken using Stratified Random Sampling sampling technique. The results of the study partially show that Islamic celebrity endorsers have a tcount value of 1.490 < ttable 1.985 and a significance value of 0.140 > 0.05, the halal label has a tcount value of 3.037 > ttable 1.985 and a significance value of 0.003 <0.05, and product quality has a value of tcount. 4.891 > t table 1.985 and a significance value of 0.000 < 0.05. So it can be concluded that partially Islamic celebrity endorser has no effect on buying interest, while the halal label and product quality affect the buying interest of Wardah cosmetics at Muhammadiyah University Sidoarjo students. Meanwhile, simultaneously Islamic celebrity endorser, halal label and product quality affect the buying interest of students at Muhammadiyah University of Sidoarjo.